Assessing the cadmium phytoremediation potential of different Solanum lycopersicum L. cultivars during their vegetative growth phase - Jia, Jibao; Dai, Huiping; Zhan, Jie; Wei, Shuhe; Skuza, Lidia; Chang, Junjun (Frontiers in Plant Science, 2025)
IntroductionSolanum nigrum L. has been a widely studied Cd hyperaccumulator. Solanum lycopersicum L. also belongs to the same family (Solanaceae) with S. nigrum. Compared to S. nigrum, the Cd accumulation characteristics and remediation potentials of seven S. lycopersicum cultivars at their maximum vegetative growth period stages (MVGPS) were determined. The advantage of the remediating method at MVGPS is to avoid Cd entering food chain via fruits at mature period.MethodsSoil pot experiments were conducted and used to determine Cd concentration in all test plants. Biomasses and some physiology index were measured either.ResultsThe results showed that the enrichment factors (EFs, the Cd concentration ratio of shoots to soils) of the tested S. nigrum and all cultivars were greater than 1. However, only the translocation factors (TFs, the Cd concentration ratio of shoots to roots) of S. nigrum and Baishite (S. lycopersicum cultivar) were higher than 1, indicating that only Baishite exhibited the main properties of a Cd hyperaccumulator. In particular, the Cd concentration (20.27 mg kg-1) in shoot of Baishite was same as that of S. nigrum, and they were the highest. Cd shoot accumulation capacity (96.1 µg plant-1) of Baishite was 17.6 % higher than S. nigrum due to its higher shoot biomass (an increase of 10.4 %). The shoot of biomass (g plant-1) in Baishite was higher than in S. nigrum. Furthermore, some index like chlorophyll content and SOD activity of Baishite were higher either, which might be part reasons for Baishite highly accumulated Cd, but other mechanisms could play more important roles.DiscussionThese findings suggested that some S. lycopersicum cultivars could have a higher Cd remediation potential, and further screening for more ideal remediation plants from crop was possible.